(untitled) (National Administration Journal, 2020)
The Internet service is essential for any company. Without telecommunication service providers it would be very complex to manage and operationalize internal and external processes in a company since a great deal of information is handled daily to obtain products and services. That is why there is a need for telecommunications companies to rely on an integrated management system and process manuals to enable continuous improvement. Therefore, the present work proposes the design of an integrated management system regarding the quality, environment, occupational health and safety for telecommunications companies.